Analisis Dampak Covid 19 Terhadap Pendapatan Pelaku Usaha Kecil Pada Kawasan Pariwisata Pantai Gemah Di Kabupaten Tulungagung - Faizal Ilham Naziri; Elok Fitriani Rafikasari (Jurnal Dinamika Ekonomi & Bisnis, 2021)
At the beginning of 2020, economic actors began to experience a drastic decrease in income due to the spread of covid 19, while one of the impacts of the spread of the covid 19 was the decline in the income of UKM in the tourism sector, this has been real experienced since March 2020 where many UKM have gone out of business, especially UKM that only belong to the home industry, Through the background which has been described, this study aims to analyze the Impact of Covid 19 on the Income of Small Business Actors in the Gemah Beach Tourism Area in Tulungagung Regency, In this study, researchers applied the use of quantitative methods and for the type of data primary data was collected randomly to 30 selected respondents, Based on the testing and processing of the data above, it gives an answer that there is a very big difference in the value of the income of small business actors in the gemah beach tourism area, where the average business actor experienced a decline of up to 50% - 75% due to the impact of this pandemic.